Pengaruh Kinerja Lingkungan dan Corporate Social Responsibility pada Perusahaan Sektor Pertambangan - Supadi, Yohanes Made; Sudana, I Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018, 2018)
The aim of this research is to investigate the influence of environmental performance and CSR Disclosure on financial performance of mining sector companies listed in Indonesia Stock Exchange. Sample company was determined by purposive sampling technique resulting 10 sample companies with 30 observations. Data was analysis ed using multiple linear regression test. The result of the study shows that the environmental performance has a positive effect on companies' financial performance. These findings imply that the existence of a company will be legitimated when there is a harmony between the value achieved by the company and the expectations of society in the social environment of the company. It indicates that e nvironmental performance is able to raise the image of the company through the improvement of the company's financial performance. Another finding shows that CSR Disclosure positively affects the companies' financial performance , implies that CSR is a form of transparent and ethical behavior that may reflect sustainable development. CSR has become the companies' strategy to keep the companies' concern in the long term.